(untitled) (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Sales Application Program Design Based Website at. Indometic was made to improve the effectiveness of the company’s performance and deliver. In addition, as a means of information about PT.Indometic . The methodology used in this design is a prototype methodology. For a depiction of the draft then used flowcharts, Context Diagram, DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), and the relationships between tables . The programming language used is PHP, some other software in use is the Operating System Windows 7 Starter 32 Bit, Mozilla Firefox Web Browser Applications, XAMPP to run the database through phpMyAdmin .